One-Pot Syntheses of Immunostimulatory Glycolipids - Schombs, Matthew (2010)
Glycolipids containing α-linked galactosyl and glucosyl moieties have been shown to possess unique immunostimulatory activity creating a need for access to diverse and anomerically pure sources of these compounds for immunological studies. To meet this demand, glycosyl iodides were enlisted in the synthesis of these biologically relevant glycoconjugates. In the first generation protocol per-O-benzyl galactosyl iodide was efficiently coupled with activated sphingosine acceptors, but fully functionalized ceramides were found to be unreactive. To overcome this obstacle, per-O-trimethylsilyl glycosyl iodides were investigated and shown to undergo highly efficient coupling with ceramide and glycerol ester acceptors. Contrary to what has been observed with other donors, we detected little difference between the reactivity of glucosyl and galactosyl iodides. The trimethylsilyl protecting groups play a dual role in activating the donor toward nucleophilic attack while at the same time providing transient protection: the silyl groups are readily removed upon methanolysis. All reactions proceeded with complete acceptor regioselectivity, eliminating the need for additional protecting group manipulations, and the desired α -anomers were formed exclusively. This three step one-pot synthetic platform provides rapid access to an important class of immunostimulatory molecules including the first reported synthesis of the glucosyl analog of the bacterial antigen BbGL-II.